Accuracy assessment of burned area products in the Orinoco basin (2010)
Burned area products derived from satellite images are used as input to determine biomass burning emissions. Appropriate assessment of the accuracy of burned area products is required to assess reliable emissions. This document provides validation results for four burned area products: GlobCarbon, MCD45, L3JRC and AQS. The study area is at the northern South American savannas along the Orinoco River since there is a rapid conversion of Amazonian forest to cattle pasture. A validation method was applied from 2001 to 2007 based on the comparison of commission and omission errors from 20 confusion matrixes with their respective efficient solution. Efficient solutions were determined using the "Pareto Boundary". This method allows estimating the potential for improving burned area algorithms as well as evaluating the effect of pixel size on accuracy. A landscape metric was used to analyze the weight of the fragments' distribution on global accuracy. It was found that all products underestimate burned area and that an increase in pixel size or border density results in larger burned area estimate errors.